2015
DOI: 10.1007/s00701-015-2417-5
|View full text |Cite
|
Sign up to set email alerts
|

A new classification and clinical results of Gamma Knife radiosurgery for cavernous sinus hemangiomas: a report of 53 cases

Abstract: Our study showed that GKS is a useful and safe therapeutic method for CaSHs as both a primary and adjuvant treatment. The new classification of CaSHs may help predict their clinical course during tumor development and treatment response after GKS. Further studies with long-term follow-up and larger numbers of cases are necessary to optimize the treatment conditions and verify the benefit of this treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 39 publications
1
11
0
2
Order By: Relevance
“…Studies have reported dysesthesia in 0-16%, paresthesia in 0-13%, deafferentation pain in 0-3.3%, dry eye syndrome in 0-22.4%, and keratitis in 0-7%. [44][45][46][47] Complications were not associated with the prior procedure in previous studies, which is consistent with our results. [48][49][50] This may be due to some differences in the mechanisms of complications in destructive procedures, such as GKRS, versus nondestructive procedures, such as MVD.…”
Section: Complications Of Gkrssupporting
confidence: 93%
“…Studies have reported dysesthesia in 0-16%, paresthesia in 0-13%, deafferentation pain in 0-3.3%, dry eye syndrome in 0-22.4%, and keratitis in 0-7%. [44][45][46][47] Complications were not associated with the prior procedure in previous studies, which is consistent with our results. [48][49][50] This may be due to some differences in the mechanisms of complications in destructive procedures, such as GKRS, versus nondestructive procedures, such as MVD.…”
Section: Complications Of Gkrssupporting
confidence: 93%
“…However, both ICH and cavernous sinus hemangioma can be asymptomatic. [ 2 , 17 ] Hemorrhage is the most common manifestation of a cerebral cavernous hemangiomas, followed by epilepsy and focal neurological deficits according to the location of the hemangioma. Some asymptomatic cerebral cavernous hemangiomas are usually discovered incidentally during a physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Intrasellar and parasellar extra-axial cavernous hemangiomas can be classified into 3 types according to the relationships among the tumor origin, expansion, and ICA on coronal MRI. [ 17 ] According to this classification, many ICHs reported in the literature belong to the mixed type (Type III), while only a few cases belong to the true intrasellar type (Type I). Lombardi divided sellar and parasellar extra-axial cavernous hemangiomas into 3 types based on the patterns of growth, namely endophytic lateral growth, endophytic medial growth, and exophytic growth.…”
Section: Discussionmentioning
confidence: 99%
“…They reported 100% tumor control rate with over 80% reduction in tumor volume in 55% of patients after a 24-month radiological follow-up period. Thirty three of the 53 patients demonstrated significant improvements in their clinical status, although two patients showed temporary clinical deterioration (20). Recently, Lee et al reported a multi-center retrospective study that included 31 CSH cases.…”
Section: █ Discussionmentioning
confidence: 99%